Pengaruh Pemberian Latihan Konsep Bobath Dan Konsep Propioseptive Neuromuscular Facilitation Terhadap Aktivitas Fungsional Pada Pasien Stroke Non Haemorragic Di RSUD Dr. Wahidin Sudiro Husodo Mojokerto - Septiyani, Nuke; , Yulisna Mutia Sari, SSt.FT.,MSc (GRS) (2016)
Background : Stroke of Non Haemorragic is a syndrome resulting from clogged of blood vessels servico-cranial caused by plaque, aterotrombosis and emboly that causing the death of brain tissue. The problem caused bystroke of non haemorragic is reflect movement disorder which decrease the ability of functional activity of the individual. To help the stroke recovery there are several training, the Bobath concept and PNF concept are the two of them. The Bobath Concept is more at the use of irreguler movement pattern or synergic pattern and primitive reflect which arise by giving sensoric stimulation to fascilitate a basic synergic mucle movement on early stage of stroke, while the PNF concept is easier to be used PNF needs a good sensoric and motoric nature of the patient since all of the movement/training will increase the neuromuscular mechanism that will provide response of activity and the increasing of functional activity occur. Objective :This research aimed to find the different effect between Bobath Concept and PNF Concept training to increase functional activity on case of non haemorragic stroke. Method : This research was an experimental, two group pre test and post test design. Group I was given a training of Bobath Concept and group II was given a training of PNF Concept toward patient of non haemorragic stroke to measure the increasing of functional activity. With Indeks Barthel measurement, the assesment is obtained before and after therapy. This research is done 3 times/week for 4 week. Result : Statistical test on effect of Bobath group was (p=0,000) therefore p<0,05, PNF group was (p=0,000) therefore p<0,05, and the two group comparison resulting effect difference of(p=0,291) therefore p>0,05 Conclusion :The Bobath training and PNF training given toward patient of non haemorragic stroke both can give improvement of functional activity, but none was significantly better. Keyword :Stroke of Non Haemorragic, Bobath Concept Training, PNF Concept Training, Functional Activity, Barthel Indeks